A Move Analysis of Happily-Ever-After Women’s Fiction Blurbs: Classic vs. Mass-Marketed Novels - Pupipat , Apisak (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2023)
Based on Gea-Valor (2005), Cacchiani (2007) and Önder (2013), this study explored the nature of moves in 40 classic (CL) and 40 mass-marketed (MM) blurbs from happily-ever-after women’s novels written or translated into English. The three research questions were: (1) What were the obligatory, conventional and optional moves in the CL and MM? (2) What were the high-frequency steps in both types, in the CL, and in the MM? and, (3) Which steps showed large differences between the CL and MM? Which steps were unique to the CL and MM? The results can be summarized as follows: First, two obligatory moves in the M2 book description were found in both types of blurbs and the M6 technical information was found only in the MM. Conventional moves populated most of the rest, along with a few of the optional moves, with M4 author’s credentials having the lowest figure. Next, regarding both types’ 17 notable steps in the six moves, the top three were M5.3 magazines and newspapers, M4.3 literary accomplishments, and M3.1 content. Finally, nine unique steps were found. The CL’s six included, from high to low, M3.5 direct compliments, M1.5 excerpts, M2.1.2 background with evaluation, M4.1 date/place of birth/death, M3.3 literary theory and style and M6.4 translator/introduction writer’s info while the MM’s three steps were M6.1 author’s contacts, M4.5 personal life, and M2.4 curiosity arousers. It is hoped that discourse analysts and EFL practitioners would benefit from this paper.